What do we need kids for? Childbearing motivations, personal values, and socio-demographic differences - Tartakovsky, Eugene; Mizrahi, Mor (Frontiers in Psychology, 2025)
IntroductionIn this study, we propose a new conceptualization of childbearing motivations and examine their links with personal values and socio-demographic variables during the preconception period.MethodTo test our model, we conducted a cross-sectional study using a stratified sample of young Israeli Jews without children (aged 18–35, n = 1,122).Results and discussionWe found that childbearing motivations form four clusters, reflecting different goals people strive to achieve through childbirth. We referred to these clusters as life enrichment, authority, preservation, and perpetuity. The four clusters formed a two-dimensional circumplex paralleling the structure of values. The pattern of connections between childbearing motivations and personal values corroborated the existence of a contextualization mechanism linking general and specific motivations. In addition, the indirect effects of socio-demographic variables on childbearing motivations through personal values showed that differences in childbearing motivations across socio-demographic groups may be partly attributed to variations in general motivational goals that characterize the groups.